Metabolic pathways and abnormalities - Evans, R; Heather, L (Elsevier, 2016)
Metabolism describes the series of chemical reactions which are concerned with the provision of energy to biological systems. They may be divided into reactions involved in energy yield (catabolism: demand exceeds supply), and energy storage (anabolism: supply exceeds demand). Regulation of these pathways is critical for homoeostasis, and derangements in metabolism are seen in a wide variety of pathological processes. Understanding metabolism is key to the treatment of many diseases, notably diabetes, as well as underpinning clinical nutritional support.